Phases in development of an interactive mobile phone-based system to support self-management of hypertension - Hallberg I; Taft C; Ranerup A; Bengtsson U; Hoffmann M; Höfer S; Kasperowski D; Mäkitalo Å Lundin M; Ring L; Rosenqvist U; Kjellgren K (Dove Medical Press, 2014)
Inger Hallberg,1,11 Charles Taft,1,11 Agneta Ranerup,2,11 Ulrika Bengtsson,1,11 Mikael Hoffmann,3,10 Stefan Höfer,4 Dick Kasperowski,5 Åsa Mäkitalo,6 Mona Lundin,6 Lena Ring,7,8 Ulf Rosenqvist,9 Karin Kjellgren1,10,11 1Institute of Health and Care Sciences, 2Department of Applied Information Technology, University of Gothenburg, Gothenburg, 3The NEPI Foundation, Linköping, Sweden; 4Department of Medical Psychology, Innsbruck Medical University, Innsbruck, Austria; 5Department of Philosophy, Linguistics and Theory of Science, 6Department of Education, Communication and Learning, University of Gothenburg, Gothenburg, 7Centre for Research Ethics and Bioethics, Uppsala University, 8Department of Use of Medical Products, Medical Products Agency, Uppsala, 9Department of Medical Specialist and Department of Medical and Health Sciences, Linköping University, Motala, 10Department of Medical and Health Sciences, Linköping University, Linköping, 11Centre for Person-Centred Care, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden Abstract: Hypertension is a significant risk factor for heart disease and stroke worldwide. Effective treatment regimens exist; however, treatment adherence rates are poor (30%–50%). Improving self-management may be a way to increase adherence to treatment. The purpose of this paper is to describe the phases in the development and preliminary evaluation of an interactive mobile phone-based system aimed at supporting patients in self-managing their hypertension. A person-centered and participatory framework emphasizing patient involvement was used. An interdisciplinary group of researchers, patients with hypertension, and health care professionals who were specialized in hypertension care designed and developed a set of questions and motivational messages for use in an interactive mobile phone-based system. Guided by the US Food and Drug Administration framework for the development of patient-reported outcome measures, the development and evaluation process comprised three major development phases (1, defining; 2, adjusting; 3, confirming the conceptual framework and delivery system) and two evaluation and refinement phases (4, collecting, analyzing, interpreting data; 5, evaluating the self-management system in clinical practice). Evaluation of new mobile health systems in a structured manner is important to understand how various factors affect the development process from both a technical and human perspective. Forthcoming analyses will evaluate the effectiveness and utility of the mobile phone-based system in supporting the self-management of hypertension. Keywords: adherence, blood pressure, cellular phone, communication, devices, person-centered care